Electronic System with Internet of Things Protocol That Contributes to the Rational Use of Water in Housing Units - Javier Vargas, Daniel Bejarano, Jeison Arango, Carlos Torres (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article presents the results of an investigation whose object of study was the design and implementation of an electronic system with Internet of Things protocol in order to contribute to the strategies of rational use of water in housing units. The results found were framed in the construction of a functional electronic prototype, with a high degree of integration to communication systems with IOT protocol useful in the implementation of smart cities. Likewise, an intervention process was carried out in a university academic community for its respective validation. Finally, it was concluded that the electronic prototype is functional, meets the standardized technical and engineering requirements, and contributes to people's awareness processes regarding the rational use of water.